Construction and characterization of a cDNA library from floral organs and fruitlets of Citrus reticulata - T. G. Zheng; W. M. Qiu; G. E. Fan; B. B. Zheng; W. W. Guo (Biologia Plantarum, 2011)
To explore and isolate genes related to flowering and fruit development, we constructed a cDNA library from floral organs and fruitlets of Ponkan mandarin (Citrus reticulata Blanco). A total of 661 high-quality expressed sequence tags (ESTs) were generated and submitted to GenBank with the accession numbers from GO343532 to GO344192. All these ESTs were assembled into 43 contigs and 296 singletons (totally 339 unigenes). The BLAST2GO software was employed to annotate the unigenes, among which 77 ones had no significant homology with the sequences in NCBI non-redundant proteins database by BLASTX analysis. Additionally, gene ontology (GO) analysis revealed an overview of sequences distribution, which implied some specially expressed genes related to flower and fruit development. Furthermore, some abundantly expressed unigenes involved in several crucial metabolic pathways related to fruit quality were highlighted and three types of homologues of miraculin-like protein2 were analyzed by both semiquantitative RT-PCR and real-time PCR. The results showed different expression profiles of these genes, which meant that they contribute distinctly to fruit development.